Peran HUMAS dalam Meningkatkan Daya Saing Madrasah Aliyah Negeri 1 Aceh Barat - Aulia Moneta; Ade Kurniawan (Program Studi Manajemen Pendidikan Islam, 2022)
Madrasah Aliyah Negeri (MAN) 1 West Aceh is one of the most favorite madrasas in West Aceh. Of course, this cannot be separated from the role of public relations which has done various things in promoting MAN 1 Aceh Barat. Public relations plays a vital role in the process of providing education. This paper aims to determine the role of Public Relations in increasing the competitiveness of MAN 1 Aceh Barat. The type of research used is descriptive qualitative research. The subjects in this study were the head of the madrasa, 1 waka from the public relations department, and 6 madrasa teachers at MAN 1 Aceh Barat. Data was collected using observation, interviews, and documentation studies. Activities in data analysis include the stages of reducing data, presenting data, and drawing conclusions. Public Relations of MAN 1 Aceh Barat has an essential role in increasing the competitiveness of madrasas. The role of public relations is carried out in two forms, namely 1) fostering internal relations with school residents by maintaining friendship and cooperation between fellow school communities and 2) fostering external relations for madrasas by maintaining relationships with outside communities such as collaborating in the fields of education, health, security, finance and make visits to schools.